Desain Mesin Compiler untuk Penganalisa Leksikal, Sintaksis, Semantik, Kode Antara dan Error Handling Pada Bahasa Pemrograman Sederhana - Fauziah Fauziah; Andez Apriansyah; Tri Ichsan Saputra; Yunan Fauzi Wijaya (Politeknik Negeri Batam, 2019)
In compilation techniques, the processes and stages carried out relate to translating source languages into target languages (object programs). Source languages are high-level programming languages that are easy to understand and easy to learn by humans, while target languages are low-level languages that are only understood by machines. In this study a compiler machine called Automatic LESSIMIC Analyzer is used which can be used to analyze, including lexical, syntactic, and semantic analysis. Compiler machines that are designed can also synthesize intermediate code, using assembler codes. The compiler engine will produce an analysis of the program code that the user enters in the form of an error message, if the program code is not in accordance with the grammar that applies generally in programming languages. In this research, the simple program code that is inputted is C ++ programming language, and successfully analyzes the lexical, semantic, syntactic, intermediate code generation and successfully detects errors from the program code entered with a success rate of 99%.